Changes in the basal dendrites of cortical pyramidal cells from alcoholic patients--a quantitative Golgi study. Issue 10 (October 1990) - Harper, C; Corbett, D
Abstract : Although a variety of pathological changes have been described in the brains of chronic alcoholic patients, there have been no studies which have addressed the question of alterations in cortical neuronal dendritic arborisation. Loss of neurons from the superior frontal gyrus and shrinkage of neurons from both the superior frontal gyrus and motor cortex has been documented in chronic alcoholic patients; these areas were chosen for this study. Using a modified rapid Golgi technique the basal dendritic arborisation of layer III pyramidal neurons was compared in 15 male alcoholic patients and 15 age-matched male controls. All parameters measuring basal dendritic arborisation were significantly less in the alcoholic cases for both the superior frontal and motor cortices. Changes in the arbor are in the terminal branches, which is consistent with other models of dendritic plasticity. Such changes may explain both permanent and reversible functional deficits in chronic alcoholic patients.